Трансляция природных мРНК. 2. Кинетические особенности трансляции наборов разных мРНК - Потапов, А.П.; Ельская, А.В. (Биополимеры и клетка, 1986)
Дан теоретический анализ стационарной кинетики трансляции наборов разных мРНК. Показана ключевая роль удельных скоростей инициации считывания разных мРНК в дифференцированной регуляции скорости их трансляции. Выявлены условия, при которых удельные скорости инициации становятся функциями конкретных последовательностей элонгаторных (терминаторных) кодонов соответствующих мРНК и удельных скоростей считывания этих кодонов. Сделан вывод о большой функциональной значимости полирибосомной организации аппарата трансляции в регуляции скорости и пропорции синтеза индивидуальных белков. Проведено теоретичний аналіз стаціонарної кінетики трансляції наборів різних мРНК. Показано ключову роль питомих швидкостей ініціації зчитування різних мРНК у диференційованій регуляції швидкості їхньої трансляції. Виявлено умови, за яких питомі швидкості ініціації стають функціями конкретних послідовностей елонгаторних (термінаторних) кодонів відповідних мРНК і питомих швидкостей зчитування цих кодонів. Зроблено висновок про велику функціональну значущість полірибосомної організації апарату трансляції в регуляції швидкості і пропорції синтезу індивідуальних білків. A theoretical analysis of steady-state kinetics of the translation system involving a number of different mRNAs is presented. The specific rates of initiations are shown to play the key role in regulation of translation of different mRNAs. Conditions under which the specific rates of initiation become the functions of the specific rates of elongator codons reading and the elongator codons sequence are analyzed. Such conditions correspond to the situation when one ribosome of polyribosomal complex catches up with another ribosome and stumbles upon it during the mRNA translation. A conclusion is drawn on great significance of the polyribosomal organization of translation apparatus in the regulation of rates and ratio of individual proteins biosynthesis.